2020
DOI: 10.1186/s12879-020-4789-2
|View full text |Cite
|
Sign up to set email alerts
|

Wound infection with Vibrio harveyi following a traumatic leg amputation after a motorboat propeller injury in Mallorca, Spain: a case report and review of literature

Abstract: Background: Vibrio spp. are aquatic bacteria that are ubiquitous in warm estuarine and marine environments, of which 12 species are currently known to cause infections in humans. So far, only five human infections with V. harveyi have been reported. Case presentation: A 26-year old patient was transferred to our center by inter-hospital air transfer from Mallorca, Spain. Seven days before, he had suffered a complete amputation injury of his left lower leg combined with an open, multi-fragment, distal femur fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 37 publications
0
24
0
1
Order By: Relevance
“…As in other studies, this finding demonstrates that most infections with Vibrio spp. involve either exposure of previously contracted wounds to seawater or injuries acquired during water-based activities [ 9 , 37 ]. The vast majority of Vibrio infections (n = 54; 86%) occurred between June and September: when water-associated recreational activities increase, high SSTs are responsible for an elevated abundance of Vibrio spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in other studies, this finding demonstrates that most infections with Vibrio spp. involve either exposure of previously contracted wounds to seawater or injuries acquired during water-based activities [ 9 , 37 ]. The vast majority of Vibrio infections (n = 54; 86%) occurred between June and September: when water-associated recreational activities increase, high SSTs are responsible for an elevated abundance of Vibrio spp.…”
Section: Discussionmentioning
confidence: 99%
“…can manifest as wound infections, ear infections, gastroenteritis, and primary septicaemia and have been predominantly reported in tropical and subtropical regions [ 6 ]. In Europe, cases are rare, and infections associated with the Mediterranean Sea [ 7 - 9 ], the Atlantic Ocean [ 10 - 12 ], or the Baltic Sea [ 13 , 14 ] have only been sporadically reported. However, a rapidly warming marine environment accompanied by an increase in extreme weather events such as heatwaves has resulted in unprecedented peak SSTs favouring the spread of Vibrio spp.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies from other provinces of South Africa, the isolation of Vibrio harveyi , V. parahaemolyticus , V. cholerae , V. mimicus , and V. vulnificus from tap, borehole, and dam in North West province ( Maje et al, 2020 ) and V. cholerae from four WWTPs located in Gauteng Province ( Dungeni et al, 2010 ) has also been reported. Health risks that an individual using these water resources could be exposed to include gastrointestinal infections caused by V. parahaemolyticus , V. mimicus , and V. fluvialis ; wound infections caused by V. vulnificus and V. harveyi ; cholera caused by V. cholerae ; and cholera-like bloody diarrhea caused by V. fluvialis ( Ramamurthy et al, 1994 ; Igbinosa and Okoh, 2010 ; Jones, 2017 ; Brehm et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aber auch bei einem entsprechendem Krankheitsbild von Reiserückkehrern muss an Infektionen mit Nicht-Cholera-Vibrionen gedacht werden. Dies verdeutlicht der Fall eines 2018 im Universitätsklinikum Hamburg-Eppendorf behandelten Patienten, der sich auf Mallorca im Rahmen einer Schiffsschraubenverletzung mit Amputation des Unterschenkels eine Wundinfektion mit V. harveyi zugezogen hatte [ 8 ]. Um in Zukunft tiefergehende Erkenntnisse über Epidemiologie, Mikrobiologie und klinische Zeichen von Infektionen mit Nicht-Cholera-Vibrionen zu gewinnen, ist neben einer zuverlässigen Surveillance dringend auch weitere Forschung zu diesen neu aufkommenden Pathogenen erforderlich.…”
Section: Resümeeunclassified